Analisis Aspek-Aspek Psikologis Siswa-Atlet Pencak Silat di Kabupaten Subang - Nurafifah, Inne; Hidayat, Yusuf; Rahmat, Alit (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
P This research aims to analyze the psychology of pencak silat student-athletes in Subang Regency from a gender perspective. Quantitative descriptive methods were used in this research with 64 samples who were pencak silat athletes from Subang Regency with 32 male student-athletes and 32 female student-athletes who had participated in pencak silat championships. The instrument used was the PSIS-R5 which was developed by Mahoney, Gabriel, & Perkins, using a Likert scale with 43 statement items. All data collected was analyzed using the Independent Sample t-Test to test the psychological differences between male and female student-athletes. The results of the analysis show that the psychology of male and female pencak silat student-athletes is significantly different. Conclusion, pencak silat student-athletes have significantly different psychology. An important implication of the results of this research is that coaching and psychological development of athletes in the form of interventions can be given to pencak silat student-athletes by considering gender categories. Keywords : Gender, Psychological Aspects, Pencak Silat, Student-athletes.